Pencegahan Stunting melalui Edukasi Masyarakat: Fokus pada Dampak Stunting dan Pola Makan Sehat dan Bergizi di Desa Pamait: Promoting Stunting Prevention through Community Education: A Focus on the Impact of Stunting and Healthy, Nutritious Eating Patterns in Pamait Village - Lisawanto, Lisawanto; Wahyunawati, Sri; Kurniaty, Harlina; Selvanus, Selvanus; Crespo, Ririn; Sinatra, Alvin; Awaliyah, Awaliyah; Aulia, Riska; Saidah, Saidah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Implementing the National Action Plan for the Acceleration of Stunting Reduction (RAN PASTI), Universities are included in the structure as Monitoring Coordinators for Evaluation of the Acceleration of Stunting Reduction. STIE Dahani Dahanai as a partner of the Regional Government carries out community service activities for the stunting prevention action program in Pamait Village, Dusun Selatan District, South Barito Regency, Central Kalimantan in 2025. This PKM was carried out on 13 - 14 January 2025 involving participants from young women, pregnant women, breastfeeding mothers, and mothers with children under five in Pamait Village. 25 participants attended this activity. This activity was carried out by 4 lecturers and students of STIE Dahani Dahanai. The methods in this PKM are observation and counseling with the aim of prevention and evaluation. The targets of the activity are young women and pregnant women, breastfeeding mothers, and mothers with children under five by providing education about stunting and its characteristics, exposure to the causes and long-term impacts as well as material about parenting, eating patterns, and good sanitation. Simulation of making healthy, balanced nutritious food using easily available ingredients. Based on the results of the pre-test and post-test, it can be seen that the participants' knowledge has increased, which indicates that this activity is useful in increasing the participants' knowledge.